2017
DOI: 10.2105/ajph.2017.303816
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Disease Outbreaks in Correctional Institutions—United States, 1998–2014

Abstract: Objectives To present the first update on the epidemiology of US foodborne correctional institution outbreaks in 20 years. Methods We analyzed data from the Centers for Disease Control and Prevention’s Foodborne Disease Outbreak Surveillance System to describe correctional institution outbreaks from 1998 to 2014 and compare them with other foodborne outbreaks. Results Two hundred foodborne outbreaks in correctional institutions were reported, resulting in 20 625 illnesses, 204 hospitalizations, and 5 death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Foodborne illnesses are a concern for correctional facilities. A study of outbreaks reported to the CDC Foodborne Outbreak Surveillance System 1998–2014 found outbreaks in correctional facilities were among the largest foodborne outbreaks in the USA each year [1]. Incarcerated persons had a rate of outbreak-related illness more than six times greater than non-incarcerated persons.…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne illnesses are a concern for correctional facilities. A study of outbreaks reported to the CDC Foodborne Outbreak Surveillance System 1998–2014 found outbreaks in correctional facilities were among the largest foodborne outbreaks in the USA each year [1]. Incarcerated persons had a rate of outbreak-related illness more than six times greater than non-incarcerated persons.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings also link incarceration to many deleterious outcomes involving health and well-being (see Massoglia and Pridemore, 2015, for a review). Imprisonment worsens indicators of population health (Schnittker et al, 2015;Wildeman, 2016) and heightens risks for both infectious (Massoglia, 2008) and foodborne illnesses (Marlow et al, 2017). Furthermore, incarceration is tied to chronic disease (Binswanger, Krueger, and Steiner, 2009;Schnittker and John, 2007), obesity (Houle, 2014), diminished mental health (Porter and Novisky, 2017;Schnittker, 2014;Schnittker, Massoglia, and Uggen, 2012), trauma exposure (Anderson, Geier, and Cahill, 2016), and hastened mortality (Binswanger et al, 2007;Patterson, 2013;Pridemore, 2014;Spaulding et al, 2011).…”
mentioning
confidence: 99%
“…According to ‘Surveillance for Foodborne Disease Out-breaks United States, 2014: Annual Report’ from the US CDC, 44.0% of foodborne disease outbreak cases reported restaurant as the location where food was prepared (12). Most of the cases are related to food prepared in a restaurant (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with western developed countries, China’s foodborne disease surveillance system still has many limitations and remains in the early stage of development in a stepwise fashion. Such as food categories implicated in foodborne disease outbreaks were 24 categories in the USA (14), no “a variety of foods”. Fruit and its products (including preserved fruit and preserves) was the second frequently reported exposed food, meat and meat products was only third in our analysis, this result is similar to that of other provinces in China (15, 16), however, the major proportion of cases of foodborne illness in western developed countries are associated with foods of animal origin (17).…”
Section: Discussionmentioning
confidence: 99%